Hypotestosterone in Male with Obesity - Liong Boy Kurniawan (Indonesian Association of Clinical Pathologist and Medical laboratory, 2021)
Obesity can be defined as the excess of body fat. The prevalence of obesity worldwide increases in the last decades andcauses a higher risk of cardiovascular diseases. Male subjects tend to develop visceral (abdominal) obesity, which producespro-inflammatory adipokines. Obesity in males is associated with low testosterone levels. Several mechanisms have beenproposed to explain the link between male obesity and hypotestosterone, including increased aromatization oftestosterone to form estradiol, suppressing the Hypothalamus-Pituitary (HPT) axis due to pro-inflammatory adipokines, anddecrease of Sex Hormone Binding Globulin (SHBG) production. Because hypotestosterone in males with obesity is afunctional but reversible condition, it is essential to screen testosterone levels in obese males for early intervention andtreatment.